Comparative efficacy of dentifrice containing sodium monofluorophosphate + calcium glycerophosphate and non-fluoridated dentifrice: A randomized, double-blind, prospective study - Satyawan G Damle; D Deoyani; Hiteshwar Bhattal; Renu Yadav; Ashish Lomba (Wolters Kluwer Medknow Publications, 2012)
Background: The efficacy of fluoridated dentifrices in caries prevention has been well documented and research into various formulations continues for a more effective dentifrice. This study evaluated the anti-caries and anti-plaque efficacy of a dentifrice containing sodium monofluorophosphate (1000 ppm) and calcium glycerophosphate, and compared it with a non-fluoridated dentifrice. Materials and Methods: A total of 595 school children (12-15 years) were divided into test (302 children) and control (293 children) groups. The test group used the dentifrice containing sodium monofluorophosphate (1000 ppm) and calcium glycerophosphate, whereas the control group was given a placebo dentifrice. Oral examination for dental caries and plaque assessment was carried out at the start of the study and the children were followed up semiannually up to 18 months. Data were analyzed using repeated-measure analysis of variance (ANOVA) followed by one-way ANOVA. Results: The values for decayed missing filled teeth (DMFT) increased from baseline to 18 month examination from 4.43±2.03 and 4.67±2.25 (P=0.175) to 5.84±2.29 and 5.13±2.30 (P=0.001) for control and test groups, respectively. Similarly, the increase in decayed missing filled surface (DMFS) values were from 6.42±4.10 and 7.06±4.77 (P=0.082) to 8.64±4.51 and 7.92±5.07 (P=0.095) for test and control groups, respectively. The mean DMFT and DMFS values increased for both the groups; however, the increase was less in test group as compared to control group. The baseline plaque score reduced from 2.94±0.72 and 2.91±0.72 (P=0.679), respectively, for control and test groups to 1.33±0.46 and 0.91±0.38 (P<0.001), respectively, at 18 month examination. Conclusion: Results revealed that the test dentifrice was effective in inhibiting the progression of plaque and control of dental caries as compared to the placebo dentifrice.